2019
DOI: 10.1016/j.foodres.2019.108545
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic composition and antioxidant properties of ex-situ conserved tomato (Solanum lycopersicum L.) germplasm

Abstract: Tomato (Solanum lycopersicum L.) local varieties represent a reservoir of genetic diversity for desirable quality traits. In this study, a representative collection of table tomato germplasm conserved ex-situ in the Portuguese Gene Bank was characterized for its polyphenols composition and antioxidant capacity. Phenolic acids, such as caffeic and p-coumaric acids bounded to a hexose and 5-O-caffeoylquinic acid, corresponded to 71-98% of the identified phenolic compounds; while the remaining fraction consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…1a and b). Similarly, Daji et al [14], Ramabulana et al [27] and Pinela et al [32] reported on precursor ions at m/z 609 and m/z 593 as flavonoids.…”
Section: Lc-ms Analysis Of Flavonoidsmentioning
confidence: 88%
“…1a and b). Similarly, Daji et al [14], Ramabulana et al [27] and Pinela et al [32] reported on precursor ions at m/z 609 and m/z 593 as flavonoids.…”
Section: Lc-ms Analysis Of Flavonoidsmentioning
confidence: 88%
“…As a result, peaks 1 ([M − H] − at m/z 341) and 2/3/4 ([M − H] − at m/z 325) were tentatively identified as caffeic acid and p-coumaric acid hexoside, respectively, as described previously in extracts of Taraxacum sect. Ruderalia [19] and Solanum lycopersicum L. [20]. Peak 5 ([M − H] − at m/z 449, tentatively identified as eriodictyol-O-hexoside, presented a UV-vis spectrum characteristic at λmax 310 nm, having been previously observed by [21] in samples of Rosa canina L. Peak 3, p-coumaric acid hexoside, was the major compound found in both extracts, presenting concentrations that ranged from 9.21 ± 0.01 mg/g extract in WP samples to 2.92 ± 0.08 mg/g extract in WO samples.…”
Section: Phenolic Composition Of I Walleriana Flowers Extractsmentioning
confidence: 99%
“…Moreover, the trials were installed under the same soil and climatic conditions and agronomic management (e.g., plantation, irrigation, pruning, phytosanitary treatments, and harvesting techniques); the plants (populations) corresponding to each accession were grown under spatial isolation by artificial barriers. Therefore, it is expected that this approach has reduced abiotic effects on the chemical composition of the analysed plant material (Pinela et al, 2019). Such plant materials consisted of: (i) axillary green shoots (or suckers) from pruning performed after the flowering period to create an optimal balance of vegetative growth and fruit production; and (ii) aerial biomass at the end of the cultivation cycle.…”
Section: Plant Materials and Samples Preparationmentioning
confidence: 99%
“…The tomato fruit is a well-documented source of dietary antioxidants such as carotenoids, vitamins, and phenolic compounds (Pinela et al, 2012(Pinela et al, , 2016(Pinela et al, , 2019, but little information is available in the literature concerning the non-edible green tissues of this plant. Some authors have already evaluate bioactive properties and chemical aspects of tomato leaves (Figueiredo-González et al, 2017Silva-Beltrán et al, 2015;Taveira et al, 2012), highlighting these by-products as promising sources of bioactive constituents, including phenolics, carotenoids, and alkaloids, for the management of Alzheimer's disease and diabetes mellitus, as well as the cytotoxic effects of alkaloid-rich extracts for gastric cancer cells.…”
Section: Introductionmentioning
confidence: 99%